Examination of Individual and Social Violence a Survey - Sözen, Mehmet Şevki; Tüzün, Birgül; Dokgöz, Halis; Fincancı, Şebnem Korur (The Bulletin of Legal Medicine, 1999)
Throughout the history of human being and nowadays aggressive behaviours and violence actions that exist in all society, but appear more evidently in our country because of long lasting absence of insight, tolerance and compromise, may threaten human life time to time. In this study, reflections of various factors to manner of behaviours are examined while dealing with existing communication ways between individuals in society. It is studied that where, how and in which conditions violence appears in social life and how much it is approved as acceptable. With the help of this study, examination of psychosocial structure of violence is aimed. A multiple choice survey including 20 questions is applied to 171 persons chosen from various age and profession groups, in different socioeconomica! and socio-cultural levels of society. 89 women and 82 men that participated in this survey are in 15-70 age group. 59 persons are university graduate, 44 persons are university student and 43 persons are graduates of high school. 24 of participants have low, 110 have middle and 37 people have high income level, 111 people are married and 99 of them have children. 44.4% of participants think that the most prevalent violence happens within the family and 65.5% of participants emphasize that financial problems are the most important cause of family violence. Only 15.8% of people support the idea that beating is a part of children education while they are growing, and 12.9% of them imply that they are irresolute about this idea. 59.7% of participants answer the question that it is relaxing to beat someone sometimes positively. The idea, that prior violence experience of people especially for the boys at adolescence are useful to defend themselves is supported by only 15.8% of all. However, 85.9% of participants, agree with the idea, that violence will increase as long as accepted by society. Our study reflects the fact that although everybody from all parts of society, at every age and role, complains of aggressive actions whether they a part in the action unintentionally or involuntarily. Key words: Violence, Individual violence, Social violence.